Convención Producción Animal y Agrodesarrollo 2022 - Díaz, María F.; Martínez, Madeleidy (Cuban Journal of Agricultural Science, 2023)
This event had an attendance of 550 participants from prestigious scientific and teaching institutions, students, organizations, enterprises, associations and national and international primary farmers. We were honored with the presence of 113 colleagues from 18 countries: Mexico, Colombia, Costa Rica, Uruguay, Chile, Brazil, Ecuador, Honduras, Argentine, Peru, Venezuela, Guatemala, Panama, Spain, Italy, France, Senegal and Benin, and Cuba.